IRON INTAKE AMONG ADOLESCENT GIRLS BASED ON FAMILY SOCIO-ECONOMIC, FREQUENT HIGH-IRON FOODS CONSUMED AND KNOWLEDGE ABOUT ANEMIA IN PANDEGLANG DISTRICT - Galih Kusuma Aji; Noer Laily; Ida Susanti (Universitas Airlangga, 2021)
Anemia is a condition with abnormalities in the red blood cells where lack of iron intake was postulated to be the main factor causing anemia. Research on iron intake, therefore, in adolescent girls is essential, specifi cally in high anemia prevalence area. This study aimed to examine the eff ect of family socio-economic factors, anemia comprehension, and ten-highest iron foods consumed on iron intake. Observational study with cross sectional design was performed, applying iron consumption as dependent variable and parents’ education, employment, income and expenditure, along with ten-highest high-iron foods consumed and knowledge about anemia as independent variables. Iron intake was collected using 3 x 24-hours food recall, and ten-highest iron-rich foods consumed was obtained with 2 x food frequency questionnaire. Family socio-economic factors (education, employment, income and expenditure) and knowledge on anemia were assessed using standard questionnaire with closed-ended interview question. The study highlighted that the average iron intake was 8.11 ± 2.94 mg/day (ranging from 3.01 to 20.43 mg/day). Obtained data showed that the occupation of father played a role in the iron intake diff erence (6.20 ± 1.72 vs 8.40 ± 2.99 mg/day for formal and informal, p <0.05). However, no diff erences were found between iron intake and education of fathers and mothers, maternal occupation, income, and expenses. Ten-highest iron-rich foods consumed did not signifi cantly correlate to the amount of iron consumption (p > 0.05). Moreover, this study in adolescent girls found that there was a negative correlation between knowledge about anemia and iron intake (r= -0.259, p <0.05). In conclusion, respondents consumed around 8 mg of iron, in average, lower than Recommended Dietary Allowance. Less amount of iron intake might be caused by scarce of high-iron sources consumption